Legal Review Of The Application Of Online Buying And Selling Transactions In E-Commerce According To Kuhperdata And Ite Law - Azni Azni; Widya Timur; Ferawati Royani; Hurairah Hurairah (JURNAL HUKUM SEHASEN, 2024)
Online buying and selling or through internet facilities today is increasingly becoming a very popular buying and selling model as a result of the development of information and communication technology. One sign of technological progress is the increasingly convenient access to the internet which makes buying and selling activities not limited by space and time, and can be done at any time, the community or business actors who previously bought and sold offline, can now use the internet for trade, production, and especially buying and selling, hence the term online buying and selling. The purpose of this study is to determine the Application of Online Buying and Selling Transactions in E-Commerce According to the Civil Code and the ITE Law. The research method used is normative legal research in the form of library research which is carried out by collecting legal materials both primary, secondary and or tertiary. The results of the research and discussion show that honorary or contract workers whose existence is the implementation of online buying and selling transactions in E-Commerce according to the Kuhperdata and ITE Laws, is the implementation of online buying and selling in principle is not much different from conventional buying and selling transactions, the only difference is the technique of the sale and purchase. Conventional buying and selling is done in the real world directly between the seller and the buyer. Meanwhile, online buying and selling is carried out using electronic media through the internet network. Mentioned in Article 1 number 2 of ITE Law Number 19 of 2016 “Electronic Transactions are legal actions carried out using computers, computer networks, and / or other electronic media. And, the implementation of electronic contracts is not only subject to Law Number 22 of 2008 as a special rule (lex specialist) but also subject to the Civil Code Book III concerning Binding as lex generalis.